Similarities in the Premises of Historical Propedeutics of Jaroslav Goll and Tomáš G. Masaryk in the 1880s - Pazderský, Roman (Dějiny – teorie – kritika, 2012)
This study offers an untraditional perspective on the mutual relation between Jaroslav Goll’s and T.G. Masaryk’s views on the theoretical and methodological principles of the historical science. The basic outline of the presentation is structured in four chapters. The first one offers a brief description of integrating elements of Masaryk’s and Goll’s thought, which originated in a shared platform of realism and positivism common to the new generation of Czech intellectuals of the end of the nineteenth century. The second chapter treats the issue of Goll’s and Masaryk’s perception of the interdisciplinary status of historiography in its relation to sociology and philosophy of history. The third and four chapters then deal with the principles of historiographic activity, focusing on the understanding of the proper subject of historiographic research, the division of history into general and special, the notion of cultural history, and the thinkers’ perception of the form which the teaching of history at universities should assume.